A Community of Writers: A Workshop Course in Writing - Peter Elbow, Pat Belanoff (McGraw Hill Higher Education, 2000)
We have written A Community of Writers for first-year college student in a one semester writing course. This book features numerous writing activities and assignments that challenge students to develop their skills by writing often, by exploring their writing processes, and by sharing their writing with others.